Displacements of hysteresis loops in magnetite nanoparticles (2012)
ABSTRACT: In this work we present a Monte Carlo study to address the effect of surface anisotropy on the exchange bias behavior in magnetite nanoparticles. Our theoretical framework is based on a three-dimensional classical Heisenberg model with nearest magnetic neighbor interactions involving realistic crystalline structure for magnetite with tetrahedral and octahedral irons. Cubic magnetocrystalline anisotropy for core spins, single-ion site anisotropy for surface spins, and interaction with a uniform external magnetic field, were considered. Our results revealed the onset of low temperature exchange bias field at high enough values of the surface anisotropy constant (KS). Our results indicate also that the strongly pinned spins at high enough surface anisotropy values are responsible for both the horizontal and vertical shifts of the hysteresis loops